SURVEY OF ACCOMPLISHMENTS IN BIM IMPLEMENTATION IN CROATIA, THE CZECH REPUBLIC, GERMANY, AND SLOVENIA (Advances in Civil and Architectural Engineering, 2021)
Building information modelling (BIM) may currently be considered the fastest developing concept in the field of construction management, aiming to become a global standard. Although the roots of the concept date back to the mid-1970s, some original expectations are still missing from its implementation. There has been a time gap between its theoretical and practical implementations. While the simultaneous development of information technologies is one reason for the implementation delay, other reasons remain unclear. This paper analyzes the gaps between theoretical and practical BIM application, as well as the legislation regarding BIM implementation in four countries (in alphabetical order: Croatia, the Czech Republic, Germany, and Slovenia). The paper additionally presents a survey of current practical BIM applications as well as general and theoretical feedback from construction projects that implemented BIM.